Depression Among Infertile Men in the Gaza Strip, Palestine: The Neglected Aspect of Fertility Care - S Baloushah; A Elsous; S Abu Eid; H Zaqou; FM Ibrahim; M Abu Shawish (JRI, 2021)
Background: Infertility is a worldwide public health problem and affects psychological aspects of males’ and females’ life. However, the problem has not been well investigated in Palestine. Therefore, the purpose of this study was to determine prevalence and predictors of depression among infertile men in the Gaza strip. Methods: A cross-sectional study was carried out among three hundred eighty five infertile males from January to December 2019. Participants were selected from three main in-vitro fertilization (IVF) centers following simple random sampling. The Arabic version of Beck Depression Inventory was used. Descriptive and inferential analyses were performed using the SPSS V22. Binary analysis was done to determine independent variables and t-test and one-way ANOVA were conducted afterwards. Logistic regression was performed to determine independent factors associated with depression symptoms. The p-value of 0.05 or less was considered statistically significant. Results: Findings showed that 42.6% (164/385) of infertile men had at least one type of depression. Severe depression was presented in 16.6% (64/164) of participants, while 13.2% (51/164) and 12.7% (49/164) showed moderate and mild depression, respectively. Predictors for depression were duration of marriage (>8 years) (CI 95%: 1.099-2.615) and at least one IVF attempt (CI 95%: 0.373-0.873). Conclusion: It has been revealed that depression is prevalent among infertile men. Marriage of long duration and several failures in IVF attempts are predictors for depressions. Psychological counseling besides medical interventions seems to be an optimal strategy to alleviate psychological distress associated with infertility.